Deciphering the Causes of Dispute Settlement of the Crime of Threatening - Rusnita Mopili (Estudiante Law Journal, 2023)
The purpose of this study was to find out what factors hindered the role of the police in solving criminal threats in the Bone Bolango Regency. The type of research used is empirical research, using data types consisting of primary data and secondary data. Data collection techniques were carried out using interviews, observation, and documentation techniques. The results showed that the factors that hindered the police in disclosing the criminal act of threatening were internal factors consisting of the loss of evidence, then the absence of witnesses, and the difficulty in determining the suspect because the suspect had run away, then there were also external factors, namely the lack of public awareness.